Cytosolic O-GlcNAcylation and PNG1 maintain Drosophila gut homeostasis by regulating proliferation and apoptosis. - Hyun-Jin Na; Lara K Abramowitz; John A Hanover (PLoS Genetics)
Tissue homeostasis requires a delicate balance between stem cell self-renewal, proliferation, and differentiation. Essential to this process is glycosylation, with both intra-and extra-cellular glycosylation being required for stem cell homeostasis. However, it remains unknown how intracellular glycosylation, O-GlcNAcylation, interfaces with cellular components of the extracellular glycosylation machinery, like the cytosolic N-glycanase NGLY1. In this study, we utilize the Drosophila gut and uncover a pathway in which O-GlcNAcylation cooperates with the NGLY1 homologue PNG1 to regulate proliferation in intestinal stem cells (ISCs) and apoptosis in differentiated enterocytes. Further, the CncC antioxidant signaling pathway and ENGase, an enzyme involved in the processing of free oligosaccharides in the cytosol, interact with O-GlcNAc and PNG1 through regulation of protein aggregates to contribute to gut maintenance. These findings reveal a complex coordinated regulation between O-GlcNAcylation and the cytosolic glycanase PNG1 critical to balancing proliferation and apoptosis to maintain gut homeostasis.